Proses metakognisi siswa dalam menyelesaikan soal literasi numerasi domain geometri dan pengukuran - Ida Rosita; Hepsi Nindiasari; Sukirwan Sukirwan (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
Numerical literacy used to the ability understanding various contexts mathematics of daily life problems. One of that success factors is metacognition influenced. An important role of metacognition process to regulating and controlling cognitive thinking. This qualitative study aims to describe students' metacognition processes in solving numeracy questions geometrical and measuring domain. The subjects who are students of class IX.F SMPN 1 Malingping, Lebak Regency. The selected subjects completed successfully the challenge of numeracy on three cognitive levels of geometry measurement domain, communicative, and willing to subjects. Collected data got from tests and interviews. The results showed that the students' metacognitive process activities occurred different qualities and tendencies. Metacognitive awareness activities are identified from solution plan, gather information and fulfill prerequisites, both in pictures or sentences. Metacognitive regulation activities are reflected to carry out planning skills execution, strategies working used formula concepts or direct to the point execution. Metacognitive evaluation activities to consider limited knowledge and results quality, correctly self-assess answer questions, an error, explain solutions, re-check and final conclusions. There are students who able an assess error and correct them, but also those who don’t correct them because self-confidence who thinks what they are doing is appropriate.